PERANCANGAN ALAT PRESS TAHU YANG ERGONOMIS PADA INDUSTRI TAHU - Taruna, Deo Rama Bintang; Suyoto (Journal of Mechanical Engineering and Applied Technology, 2025)
The rapid development of technology has had a major impact on people's lives in many fields, such as information, transportation, business, and others. The industry knows that households often use conventional equipment to process food. The tools used are usually simple and not ideal during the tofu making process. Researchers want to improve existing tofu presses by making machines that are more comfortable for operators and more efficient and effective, as well as reducing the risk of fatigue and danger to operators. For this research, the 4D Research and Development (RnD) development model was used. This design discusses the comparison of ergonomics, effectiveness and effectiveness of tofu press tools.